Requirements for the identification and classification of leases in accordance with International Financial Reporting Standards (IFRS) - A comparative study with the Financial Accounting System(SCF) - - Kadri, Abdelkader (Finance and Business Economies Review, 2020)
This study presents the most important requirements for identifying and classifying leases in accordance with International Financial Reporting Standards, as well as presenting the requirements for identifying and classifying leases included in the financial accounting system, and through the above, the most important differences between them can be drawn. This comparison will allow us to see the degree of convergence between the Financial Accounting System and the International Financial reporting Standards (IFRS16).